Vector Error Correction Model for Cointegration Analysis of Factors Affecting Indonesia's Economic Growth during the Pandemic Period - Rizqa Fajriaty Fitri MY; Dina Fitria; Syafriandi Syafriandi; Zilrahmi (UNP Journal of Statistics and Data Science, 2023)
Stabel economic growth is the ultimate goal of monetary policy s seen from the stability of the rupiah. The economic situation has decreased due to the spread of Covid-19. In an effort to stabilize the economy, the relationship between factors supporting Indonesia's economic growth is analyzed using the VECM approach. This approach is able to determine the long-term and short-term relationships of time series data. The model results after fulfilling several tests are three significant equations. The model explains that there is an effect in the short term of the inflation and BI Rate variables on inflation as well as the inverse effect between BI-rate one period earlier on the exchange rate. The cointegration coefficient is negative, it indicates that there is a short-term to long-term adjustment mechanism that occurs in the inflation variable. The two cointegration equations for the long term show that for the long term, inflation can be positively influenced by the visa variable. Variable BI-rate in the long run is influenced by the variable exchange rate and visa. The VECM model can explain more than 50% of the variables.